Rate based congestion control scheme for ABR service in ATM networks :|ba three-factor congestion detection approach - Tiong, Anderson Ing Heng. (Universiti Malaysia Sarawak, UNIMAS, 2000)
The convergence of data, audio and video has made Asynchronous Transfer Mode (ATM) a good platform for supporting multimedia applications. ATM network has the ability to support and deliver data, audio and video traffic on same shared network. The available bit rate (ABR) service of ATM is designed to efficiently support data traffic. The ATM traffic management 4.0 involves the design of a set of mechanisms which ensure that the network bandwidth, buffer and other resources are efficiently utilized as well as meeting the quality of service (QOS) guarantees given to the source as part of the traffic contract.